Damages and failures of GRP pipes - Kuliczkowski, Andrzej (Instal, 2022)
The paper presents the most common errors made at the stage of installing pipes, together with possible causes of these errors and the ways of avoiding them. An example of possible damage to GRP pipes, which were examined using the CCTV technique, is provided. Tests were performed in one Polish city and covered two stages, immediately after the pipes were commissioned, and then again 14 months later. The investment covered sections of sewers that had a diameter of 300 mm and 400 mm. The observed damage is shown in 7 photos. Other examples of GRP pipe failures, from both Poland and abroad, are also provided in the paper.